PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN COORPORATE (CSR) DAN DAMPAKNYA TERHADAP REAKSI INVESTOR (Students' Journal of Accounting and Banking, 2015)
This study aims to determine the effect of company characteristics on the disclosure of corporate social responsibility (csr) and its impact on investor reaction. Population in this research are manufacturing companies listed on the stock exchange Indonesia in 2012-2014. The sample in this study were taken by purposive sampling method. Data were analyzed by using test Partial Least Square (PLS). Results of testing the first hypothesis of variable size companies positive effect on CSR, In the second hypothesis is the variable profitability in the proxy with ROA positive effect on CSR, In the third hypothesis is the variable profile companies positive effect on CSR, In the fourth hypothesis of variable size commissioners positive effect on CSR, On the fifth hypothesis that institutional ownership variable has a positive effect on the disclosure of CSR, In the sixth hypothesis that CSR variable positively affects the disclosure Abnormal Return, In the seventh hypothesis that CSR variable positive effect on the disclosure of share volume.Keywords: Company Size, Profitability, Company Profile, BOC, Institutional Ownership, Abnormal Return, Volume Stocks, CSR